Effects of Gender, Sterilization, and Environment on the Spatial Distribution of Free-Roaming Dogs: An Intervention Study in an Urban Setting - Melo, Saulo Nascimento de; da Silva, Eduardo Sergio; Barbosa, David Soeiro; Teixeira-Neto, Rafael Gonçalves; Lacorte, Gustavo Augusto; Horta, Marco Aurélio Pereira; Cardoso, Diogo Tavares; Werneck, Guilherme Loureiro; Struchiner, Claudio José; Belo, Vinícius Silva (Frontiers in Veterinary Science, 2020)
Information concerning the factors affecting the circulation and distribution of free-roaming dogs is crucial in developing control actions and limiting the spread of zoonoses. The present study analyzes the influence of gender, sterilization and environment on the spatial distribution of free-roaming dogs in urban settings. Animals were captured/recaptured in seven consecutive morning sampling efforts conducted at two-monthly intervals in control and intervention areas in a medium-size town in southeastern Brazil. Capture locations were georeferenced and captured animals were microchipped before being released at their original capture sites. Dogs captured in the intervention area were subjected additionally to surgical sterilization prior to release. Home range (HR) areas were calculated by applying the minimum convex polygon method to dogs that had been captured at least three times. Land coverage zones were determined from satellite images and overlaid on maps of the study areas along with the locations of 22 commercial food outlets. HR areas showed a global mean of 448m² and a median of 28 m2, values that were smaller than those reported previously for dogs in rural regions. The median HR of females (64.m2) was higher than that of males (15.m2), while median HRs of animals in the control and intervention areas were similar (27 and 28.5m², respectively). Variability of HR was high, although animals with small HRs predominated. Free-roaming dogs grouped primarily in urbanized and transitional regions, and their spatial distribution was positively correlated with locations of commercial food outlets. While sterilization did not influence HR size, the search for food was a key factor in determining mobility and spatial aggregation of free-roaming dogs. Our findings are pertinent in understanding the ecology of free-roaming dogs in urban environments and will be applicable to strategies aimed at promoting animal welfare and preventing the dissemination of zoonoses.